Skin microbiota of oxazolone-induced contact hypersensitivity mouse model - Mäenpää, Kuunsäde; Wang, Shuyuan; Ilves, Marit; El-Nezami, Hani; Alenius, Harri; Sinkko, Hanna; Karisola, Piia (PLOS ONE, 2022)
Contact allergy is a common skin allergy, which can be studied utilising contact hypersensitivity (CHS) animal model. However, it is not clear, whether CHS is a suitable model to investigate skin microbiota interactions. We characterised the effect of contact dermatitis on the skin microbiota and studied the biological effects of oxazolone (OXA) -induced inflammation on skin thickness, immune cell numbers and changes of the microbiota in CHS mouse model (n = 72) for 28 days. Through 16S rRNA gene sequencing we defined the composition of bacterial communities and associations of bacteria with inflammation. We observed that the vehicle solution of acetone and olive oil induced bacterial community changes on day 1, and OXA-induced changes were observed mainly on day 7. Many of the notably enriched bacteria present in the OXA-challenged positive group represented the genus Faecalibaculum which were most likely derived from the cage environment. Additionally, skin inflammation correlated negatively with Streptococcus, which is considered a native skin bacterium, and positively with Muribacter muris, which is typical in oral environment. Skin inflammation favoured colonisation of cage-derived faecal bacteria, and additionally mouse grooming transferred oral bacteria on the skin. Due to the observed changes, we conclude that CHS model could be used for certain skin microbiome-related research set-ups. However, since vehicle exposure can alter the skin microbiome as such, future studies should include considerations such as careful control sampling and statistical tests to account for potential confounding factors.